A prospective study exploring the experience of rehabilitation health professionals in implementing the 5 A`s strategy in addressing risk factors for non-communicable diseases - Vearey, Gillion (Department of Health and Rehabilitation Sciences, 2026)
Background: The growing epidemic of non-communicable diseases (NCDs) has a significant impact globally and locally in South Africa, not only on mortality rates, but also morbidity; increasing the risk of disability and decreasing the quality of life of people affected by these diseases. Behaviour Change interventions such as Motivational Interviewing (MI) and Five A's (5A's), have been developed and implemented to address the four behavioural risk factors causing NCDs. Method: A mixed method was used to 1) assess the use of MI in a South African context to address health risks for NCD`s through a scoping review, 2) assess the Scale of Staff Valence(SSV) in using MI in routine patient consultations by making us of a cross-sectional survey and an adapted Staff Valence questionnaire, and 3) the experience of Rehabilitation Health Professionals (RHPs) in implementing MI in a focus group discussion. Results: The original search identified 22 articles for the scoping review, 11 articles were excluded by title, 2 were excluded by abstract and 1 excluded by full text, 8 articles were included in the review. All the studies were based in the Western Cape Province. Diabetes and CVD were the most common conditions discussed. Most studies delivered training over 3-4days with 2 or more days of follow-up. Outcomes showed benefits of being more equipped to deliver MI to patients with NCDs, however barriers such as appropriate venues, buy in from other staff, and difficulties building rapport with some patients were also reported. Fifteen RHPs participated in this study, with 11 RHPs having more than 5 years' experience in their professional field. For the SSV scores, where a higher score reflects a positive result, for capability the average score was 28 (80%) with a standard deviation (SD) 2.4 under opportunity the average score was 66 (86%) with SD 6.6; and under motivation average score was 31 (90%) with SD 2.2. There was a statistical difference in opportunity across the level of experience (p< 0.05). These high scores confirm RHPs staff readiness in implementing behaviour change. Two themes emerged following the qualitative analysis of the RHPs' experiences in implementing the 5A's approach, namely 1) quality of the 5A's which developed from challenges and benefits of this framework as well as the impact of improved knowledge around behaviour change, and 2) impact of the clinical setting which compared the range of clinical settings RHPs practice in and the contact time available to implement the 5A's. Discussion and Conclusion MI and the 5A's can be considered a feasible approach to addressing health risk behaviours related to NCDs in South Africa. RHPs discussed the value and benefits of training and equipping in behaviour change strategies. However, barriers and challenges do exist, such as the limited patient contact time and the stage of behaviour change of each patient, influencing the effectiveness of this approach; especially in an acute setting. RHPs practicing in a subacute or outpatient setting are better suited to implement such an approach considering their contact time to build rapport with patients. These RHPs may be a more appropriate study population for future research. The 5A's framework and motivational interviewing can have a significant impact on NCDs in SA, further research is required to determine the long-term effects of such interventions.